Tipologi Rumah Desa Wisata di Dusun Ngluwuk Desa Batik Gedhog Tuban - Santri, Tyas (RUAS, 2017)
Indonesia is a country rich in tribes, nations, customs, culture, natural resources and also tourist villages. Tourism village in Indonesia spread in various regions from Sabang to Merauke, and this tourist village has each characteristic in accordance with the region, one example is one village in the village of batik gedhog that is in Ngluwuk hamlet, Kedungrejo village, Kerek District, Tuban Regency, East Java which has a distinctive cultural identity and building typology. The study of house typology in Ngluwuk gedhog batik village Tuban is using descriptive-qualitative method with typology approach. The criteria of samplings selection are based on authenticity of building shape aspect and recommendation from local society. Through this study the authors can identify the characteristics of the typology of village tourist architecture in Ngluwuk Hamlet. The shape and appearance of the house building in Ngluwuk Hamlet is a traditional tropical-style building with facade design using ornaments and the proportion of the facade and the inner room tend to be symmetrical, using the roof "tekuk lulang", Through this study it is expected the local government can educate people who have a house with the shape which is still unique would be able to maintain its authenticity. By maintaining and preserving a typical home typology, it will increasingly attract tourists to visit and enjoy the village atmosphere and buy gedhog batik from the villagers.